King of the pond - Sommer, Carl, 1930-; Budwine, Greg (Houston, Tex. : Advance Pub., 2000)
Tombo, the biggest, fastest, and strongest tadpole in the pond, teases and chases all the other tadpoles, but he comes to regret his bullying when he turns into the smallest, slowest, and weakest frog.
Keywords: Tadpoles -- Fiction; Frogs -- Fiction; Bullying -- Fiction